Anaerobic performance profiling in elite amateur boxers - Venckunas, T.; Bruzas, V.; Snieckus, A.; Stasiule, L.; Kniubaite, A.; Mickevicius, M.; Kamanduli, S.; Stasiulis, A. (Sports, 2024)
While anaerobic fitness is highly important for the performance in Olympic (amateur) boxing, the relationship between anaerobic performance metrics is poorly understood, and profiling boxers according to their anaerobic capacity is still a challenge. With the current study in elite amateur boxers, we aimed to compare the metabolic and cardiovascular responses to different maximal tests and the intercorrelations between performance indices (peak and mean power, duration of the test, punching frequency) of several all-out tests and their correlation to physiological response metrics (blood lactate and heart rate, HR). Twelve male Olympic boxers performed a battery of tests, including 30 s Wingate cycling and arm cranking, boxing bag punching, steep uphill treadmill running to exhaustion, and progressive treadmill running VO2max test. Performance indices of different anaerobic tests were not closely correlated except for the duration of uphill running with body weight scaled (relative) peak and mean power produced during Wingate cycling test and absolute mean power of both Wingate tests. The number of punches landed on a bag per 30 s was associated only with relative power achieved during Wingate cycling test. HRpeak but not peak lactate response correlated strongly across exercise tasks. Finally, no correlation between the highly developed aerobic and anaerobic capacity, suggests a complex picture of the adaptation in elite amateur boxers.